Students’ Self-Confidence And Their Speaking Performance During Online Learning - Permatasari, Seylla; Failasofah, Failasofah; Volya, Duti (Universitas Batanghari Jambi, 2024)
This study aims to determine the significant correlation between students’ self-confidence and speaking performance during online learning for the whole semester. This study conducted a quantitative correlational research design. The sample of this study was students in the 2020 class at one university in Jambi. The data was collected with a self-evaluation questionnaire with close-ended questions. The questionnaire in the form of Google Forms was distributed via WhatsApp to 104 respondents. The data was analysed using SPSS version 25, and the correlation between the two variables was analyzed using Spearman correlation. The study revealed a significant correlation between students' self-confidence and speaking performance during online learning. The evaluation results also showed that their low level of self-confidence made their speaking performance not at a reasonable level either.